GEOCHEMISTRY OF TONALITE FORMATION IN THE SUMSUNUR BATHOLITH, EASTERN SAYAN - Grebenshchikova V.I.; Koval P.V. (My University, 2004)
The geochemistry of rocks of the Sumsunur granitoid batholith in the Eastern Sayan was presented. The rocks of batholith were characterized by, on the one hand, by geochemical affinity with the host amphibolite crust rocks of Gargan block and, on the other hand, by enrichment in incompatible mantle-derived elements, including those compatible with the continental and basaltic crust. The principle features of the granitoid association were its low petrochemical alkalinity, high Na/K ratio, low contents of several typical granitophile elements, and high K/Rb ratios. The protolith consisted of Archean amphibolites of the Gargan block, whose chemical composition was close to the average lower crustal composition.